Affix rivalry in French demonym formation: The role of linguistic and non-linguistic parameters. (March 2023) - Thuilier, Juliette; Tribout, Delphine; Wauquier, Marine
Abstract : Affix rivalry is defined as the phenomenon of morphological competition where affixes and meaning are in a many-to-one relationship. Because of their poor semantic content, demonyms are perfect candidates for the investigation of selectional constraints in such a context. Indeed the morphological processes they originate from are characterized by their shared, straightfoward semantic relation, as they denote inhabitants linked to the toponym they derive from, which allows for the apparently simplified scrutinization of non-semantic properties. Investigations suggest a more nuanced and complex reality. The present study provides a quantitative and statistical investigation of the rivalry between French - ois, - ais, - ien and - éen suffixes. It notably relies on phonological and morphological features. Its contribution pertains to the use of statistical modeling to provide a quantitative description and to the integration of extralinguistic features on the nature of geographical proximity in a quantitative approach. The study shows that while the model cannot accurately predict the suffix of a given demonym based on these features, it still draws on the main tendencies underlying affix rivalry in the formation of French demonyms.